Perbaikan Manajemen Pakan Silase untuk Keberlanjutan Usaha Peternakan Sapi di Era New Normal pada Kelompok Ternak Bago Mulyo - Rizki Amalia Nurfitriani; Nur Muhamad; Mira Andriani; Niswatin Hasanah (Indonesian Journal Publisher, 2021)
Feeding independence is one of the target achievements desired by every farmer. One of them is the Bago Mulyo livestock group. The Bago Mulyo livestock group is a livestock group located in Gumukmas District, Jember Regency. Several problems of the Bago Mulyo Livestock Group which reduce production by 5% because the prices of production facilities (seeds, fertilizers, pesticides, and feed) are expensive and the distribution is not smooth; the need for food will increase by 5% due to panic buying and food supplies. The distribution of feed was not optimal, making farmers have to find solutions so that feed ingredients are still available. One solution is to utilize existing feed ingredients and maintain their feed quality until they are available throughout the year, namely by silage method. The implementation of the service consists of several activities, the first was coordination with the head of the Bago Mulyo livestock group, purchased silage materials, simulated modified silo tools, implementation of community service, and surveying the results of community service activities. The results of the community service survey which have shown that 100% of farmers who participate in the service activities understand silage technology with the addition of silo modification from previously only 43% who understand silage technology. The conclusion is an increase in understanding of silage technology which is one of the indicators of support for the service team in carrying out service activities for the Bago Mulyo Livestock Group, so that this technology can be applied properly for the sustainability of the cattle business in the Livestock Group.